Standardi in zakonski predpisi za pripravo publikacij - Jamar, Nina (Knjižnica, 2021)
Purpose: This paper presents the overview over the international standards and legal regulations for formation of publications. We present how the librarian’s expertise can help to equip publications with data. Methodology/approach: We reviewed international standards and regulations for the formation of publications. They are presented in general but the main focus is on the content of each standard. Results: Most international standards are intended for the formation of periodicals (SIST ISO 4, SIST ISO 8, SIST ISO 18, SIST ISO 214, SIST ISO 215). Other international standards regarding the formation of publications are focused on the formation of title page of books, indexes, bibliographic citations. The existing international standards remind us to which parts of publications we should (especially as librarians) pay attention. Research limitation: We limited the review to the parts of the content of standards and legal regulations for the formation of publications, which are in line with the formation of publications published at Music School Jesenice. Originality/practical implications: The data about publication are not only needed by catalogers, but also by researchers and publicists for the correct citation of bibliographic sources.
Keywords: cataloging; Glasbena šola Jesenice; Katalogizacija; Music School Jesenice; publications; publikacije; publishing; regulations; standardi; standards; zakonski predpisi; Založništvo